2018
DOI: 10.1002/open.201800108
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship and Prediction of the Electron‐Transfer Potential of the Xanthones Series

Abstract: The structure–activity relationships of 31 xanthones were analyzed by using the ferric reducing antioxidant power (FRAP) assay to determine their electron‐transfer (ET) potential. It was proven that the ET potential of xanthones was dominated by four moieties (i.e. hydroquinone moiety, 5,6‐catechol moiety, 6,7‐catechol moiety, and 7,8‐catechol moiety) and was only slightly affected by other structural features, including a single phenolic OH group, the resorcinol moiety, the transannular dihydroxy moiety, a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Besides the 3- O -galactosylation process, other structural factors may also affect the antioxidant activity of phytophenols, such as C -glycosidation, glucuronidation, isoprenylation, methylation, geometrical configuration, and p -coumaroylation [32,52,53,54,55,56]. However, the effects of all these structural factors were thought to be concentrated in the propagation step.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the 3- O -galactosylation process, other structural factors may also affect the antioxidant activity of phytophenols, such as C -glycosidation, glucuronidation, isoprenylation, methylation, geometrical configuration, and p -coumaroylation [32,52,53,54,55,56]. However, the effects of all these structural factors were thought to be concentrated in the propagation step.…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of redox chemistry, quercetin ortho-quinone is virtually an oxidized form of quercetin. The ortho-quinone moiety can be achieved through catechol oxidation by multiple pathways, including electron-transfer (ET) plus proton-transfer (PT) [75][76][77][78], hydrogen-abstraction [79][80][81], the ET pathway alone [82][83][84], or even enzymatic oxidation [25,26]. Therefore, it is very difficult for quercetin ortho-quinone to be further oxidized, suggesting that quercetin ortho-quinone is a weak antioxidant [79].…”
Section: Resultsmentioning
confidence: 99%
“…The co-existence and high relevance between catecholic flavonols and the Diels-Alder dimers have further indicated that the Diels-Alder dimers were the metabolites of catecholic flavonols in plants. During plant metabolism, quite a few factors can oxidize catecholic moieties to orthoquinone, including bio-enzymes (e.g., catechol oxidase and aurone synthase) [25,26,85], iron [83,86], LPO [86], and free radicals [75]. Of these, iron and LPO are relevant to ferroptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A hydrogen atom is abstracted from the butein-4-O-radical by excess DPPH • to form butein quinone ( Figure 4A). Finally, the catechol moiety is easily oxidized to quinone [65][66][67][68][69]. However, some of the butein-4-O-radicals can produce a butein dimer, through radical resonance, radical adduct formation, and subsequent keto-enol tautomerization [8] ( Figure 5A).…”
Section: Resultsmentioning
confidence: 99%